Roman mirrors between the Ticino and Comasco districs (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2021)
The article lists the mirrors found between the Verbano-Ticino and Como areas: they are about 70. The most common types prevail: bronze, mostly circular, but also rectangular. They spread between the age of Augustus and the first half of the first century A.D., when, at the end of Romanization, a new female identity was created.
Keywords: Mirrors; Romanization; Ticino district; Comasco; Roman women